The 2–2–2–20–20 concept for supraacetabular schanz screw insertion without additional radiography. (September 2021) - Schwarz, A.M.; Hohenberger, G.M.; Grechenig, P.; Kerner, A.; Gänsslen, A.; Staresinic, M.; Bakota, B.
Highlights: We evaluated a new technique in application of supraacetabular schanz screws without image intensifier guidance. Respecting the anatomical landmarks, pre- and intraoperative fluoroscopy can be avoided. According to the described anatomical data, we defined a 2–2–2–20–20 concept. Starting with a 2 cm skin incision 2 cm distal and 2 cm medial to the ASIS with a drill angulation of 20° inferior and 20° lateral orientation. Using this technique, all schanz screws could be sufficiently inserted without intraprocedural x-ray imaging. Abstract: Purpose: Application of supraacetabular Schanz screws is usually performed under image intensifier guidance. The aim of this study was to perform it without imaging, with the hypothesis that, respecting anatomical landmarks, pre- and intraoperative fluoroscopy can be avoided. Material & Methods: Insertion of the supra-acetabular Schanz screws was performed by two trauma surgery residents in a study sample of 14 human adult cadavers which had been embalmed by use of Thiel`s method. With cadavers placed in supine position, the anterior superior iliac spine (ASIS) was palpated. Starting from this landmark, 2 cm were measured in a distal and 2 cm in the medial direction. At this point, a 2 cm long oblique skin incision was performed. Through this approach, 150 mm Schanz screws were drilled bilaterally into the supra-acetabular corridor with an angulation of 20° to distal as well as 20° to medial. Following screw application, combined obturator oblique-outlet views (COOO) were taken bilaterally in each specimen by use of an Arcadis© Orbic 3D C-arm to prove the screw position. Six of the specimens underwent a 3D-CT-scan. Images were evaluated concerning correct screw positioning by a further traumatologist. Skin and subcutaneous tissues were removed in the ilioinguinal region and possible lesions to the lateral femoral cutaneous nerve (LFCN) or to the joint capsule were evaluated. Results: The sample consisted of eight pelves from female and six pelves from male cadavers. During radiographic evaluation of the COOO-scans (14 specimens) and the 3D-scans (6 specimens), the Schanz screws were placed inside the supra-acetabular corridor in all specimens (14/14). During dissections, no intracapsular screw placements or LFCN lesions were found. Conclusion: According to the described anatomical data, we defined a 2–2–2–20–20 concept, starting with a 2 cm skin incision 2 cm distal and 2 cm medial to the ASIS with a drill angulation of 20° inferior and 20° lateral orientation. Using this technique, all Schanz screws could be sufficiently inserted without intraprocedural x-ray imaging.